Identification of Horseshoe Crab in the Paluh Sembilang River Estuary,Langkat Regency, North Sumatera Province - Indah Tria Suci; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Horseshoe crab inhabit the Paluh Sembilang estuary. Information on the types of horseshoe crab from that area is almost none. To understand the species of horseshoe crabs present in the study area, a research has been conducted in April 2019. Samplings   were conducted in along the Paluh Sembilang, everyday for two weeks period. The horseshoe crabs were caught using a mini trawl (mesh size 50 mm). Morphometrical and meristical characteristics were analyzed descriptively. The horseshoe crabs sampled were identified. There were 138 horseshoe crabs, (67 males and 71 females) and they were consisted of two species, namely Tachypleus tridentatus (61 males and 66 females) and Carcinoscorpius rotundicauda (6 males and 5 females). The morphological characteristics of those species were as follown: T. tridentatus was large (33.08-34.89 cm), greenish gray colored. While C. rotundicauda was smaller (27.38-25.8 cm), dark green to greenish brown colored. Relative growth pattern shown that in both species, the growth of male is faster than that of the female.Keywords: Tachypleus tridentatus,Carcinoscorpius rotundicauda, Horseshoe Crab, Paluh Sembilang Estuary, Relative Growth.